Low-Cost Private Schools in Tanzania : A Descriptive Analysis - Sabarwal, Shwetlena; Sununtnasuk, Celeste; Ramachandran, Deepika (World Bank, Washington, DC, 2020)
This paper discusses the potential role of low-cost private secondary schools in Tanzania. The share of private enrollment has been negatively correlated with the availability of public schools. With the 2016 Fee-Free Basic Education Policy, the public secondary education system is experiencing significant demand pressures. The government has limited resources to address these pressures. Using micro-data from the Morogoro region, the paper finds that private schools have excess capacity that can allow for absorption of additional students at relatively low cost through potential public-private partnerships. The paper finds no evidence that service delivery or student performance is worse in private schools relative to their public counterparts. These findings provide empirical evidence on some key enabling conditions for potential public-private partnerships for secondary education in Tanzania.